PERBEDAAN KONTAMINASI TELUR SOIL TRANSMITTED HELMINTH PADA TANAH DI DAERAH PEDESAAN DAN PERKOTAAN - Alvan Muhammad Hibatullah Santoso; Hanna Mutiara; Giska Tri Putri; Jhons Fatriyadi Suwandi (Medula, 2023)
Soil Transmitted Helminth is an infection that causes malnutrition, anemia, growth retardation. Transmission is through contact with eggs or larvae in the soil. Cases of STH infection in Indonesia are high in areas of poor sanitation, poor hygiene and lack of understanding of clean and healthy lifestyles. Therefore, this study aims to determine the contamination of STH eggs on soil in rural and urban areas. This research is a cross-sectional study with purposive sampling. The number of samples is 90 soil sample points in rural and urban areas and then the univariate and bivariate analysis tests are carried out using the pearson chi-square Test. The number of STH contamination in rural areas was 29 out of 90 samples with 26 samples of Ascaris lumbricoides, 2 samples of Hookworm, and 1 sample of Trichuris trichiura. STH egg contamination in urban areas was 22 out of 90 samples with details of 17 samples of Ascaris lumbricoides, 3 samples of Hookworm, and 2 samples of Trichuris trichiura. Based on the results of the pearson chi-square Test analysis, a p-value of 0.467 was obtained. There is no difference in contamination of STH eggs on soil in rural and urban areas.